The influence of microbial-based inoculants on N sub(2)O emissions from soil planted with corn (Zea mays L.) under greenhouse conditions with different nitrogen fertilizer regimens - Calvo, Pamela; Watts, Dexter B; Kloepper, Joseph W; Torbert, HAllen (Canadian journal of microbiology, 2016)
Nitrous oxide (N sub(2)O) emissions are increasing at an unprecedented rate owing to the increased use of nitrogen (N) fertilizers. Thus, new innovative management tools are needed to reduce emissions. One potential approach is the use of microbial inoculants in agricultural production. In a previous incubation study, we observed reductions in N sub(2)O emissions when microbial-based inoculants were added to soil (no plants present) with N fertilizers under laboratory incubations. This present study evaluated the effects of microbial-based inoculants on N sub(2)O and carbon dioxide (CO sub(2)) emissions when applied to soil planted with corn (Zea mays L.) under controlled greenhouse conditions. Inoculant treatments consisted of (i) SoilBuilder (SB), (ii) a metabolite extract of SoilBuilder (SBF), and (iii) a mixture of 4 strains of plant-growth-promoting Bacillus spp. (BM). Experiments included an unfertilized control and 3 N fertilizers: urea, urea - ammonium nitrate with 32% N (UAN-32), and calcium - ammonium nitrate with 17% N (CAN-17). Cumulative N sub(2)O fluxes from pots 41 days after planting showed significant reductions in N sub(2)O of 15% (SB), 41% (BM), and 28% (SBF) with CAN-17 fertilizer. When UAN-32 was used, reductions of 34% (SB), 35% (SBF), and 49% (BM) were obtained. However, no reductions in N sub(2)O emissions occurred with urea. Microbial-based inoculants did not affect total CO sub(2) emissions from any of the fertilized treatments or the unfertilized control. N uptake was increased by an average of 56% with microbial inoculants compared with the control (nonmicrobial-based treatments). Significant increases in plant height, SPAD chlorophyll readings, and fresh and dry shoot mass were also observed when the microbial-based treatments were applied (with and without N). Overall, results demonstrate that microbial inoculants can reduce N sub(2)O emissions following fertilizer application depending on the N fertilizer type used and can enhance N uptake and plant growth. Future studies are planned to evaluate the effectiveness of these microbial inoculants in field-based trials and determine the mechanisms involved in N sub(2)O reduction.Original Abstract: Les emissions d'oxyde nitreux (N sub(2)O) sont en hausse a un rythme sans precedent en raison d'une augmentation de l'usage d'engrais azotes. Des lors, des outils de gestion novateurs s'imposent afin de reduire les emissions. L'une des approches possibles est de recourir a des inoculants microbiens dans la production agricole. Dans une etude anterieure, nous avons observe une diminution des emissions de N sub(2)O lorsque des inoculants a base microbienne furent ajoutes au sol (en l'absence de plantes) en compagnie d'engrais azotes dans des conditions d'incubation en laboratoire. La presente etude a evalue l'incidence des inoculants a base microbienne sur les emissions de N sub(2)O et de dioxyde de carbone (CO sub(2)) lorsqu'il etaient appliques a un sol plante de mais (Zea mays L.) dans des conditions controlees en serre. Les traitements avec inoculants se declinaient comme suit : (i) SoilBuilder (SB), (ii) un extrait de metabolites de SoilBuilder (SBF), et (iii) un melange de 4 souches de Bacillus spp. favorisant la croissance vegetale (BM). Les experiences comportaient un temoin non fertilise et trois engrais azotes : uree, uree - nitrate d'ammonium a 32 % de N (UAN-32), et calcium - nitrate d'ammonium a 17 % de N. Les emanations cumulatives de N sub(2)O des pots 41 jours apres la plantation ont presente des diminutions significatives de 15 % (SB), 41 % (BM) et 28 % (SBF) en presence d'engrais CAN-17. Lorsqu'on a employe le UAN-32, il y a eu diminution de 34 % (SB), 35 % (SBF) et 49 % (BM). Or, aucune diminution des emissions de N sub(2)O ne s'est produite en utilisant l'uree. Les inoculants a base de microbes n'ont pas eu d'incidence sur les emissions totales de CO sub(2), peu importe le traitement de fertilisation, y compris le temoin sans fertilisation. Par rapport au temoin (sans traitement a base de microbes), la captation d'azote a subi une hausse moyenne de 56 % suite a l'usage d'inoculants bacteriens. On a egalement observe des hausses significatives de la taille des plantes, des mesures de chlorophylle par un dispositif SPAD, et des poids frais et sec des pousses des suites de l'application de traitements a base de microbes (avec ou sans N). Dans l'ensemble, les resultats demontrent que les inoculants microbiens sont en mesure de diminuer les emissions de N sub(2)O apres l'application d'engrais selon le type d'engrais azote utilise et de favoriser la captation d'azote de meme que la croissance vegetale. On prevoit mener des etudes ulterieures sur l'efficacite des inoculants microbiens dans des essais sur le terrain et sur les mecanismes rendant possible la diminution de N sub(2)O. [Traduit par la Redaction]